Detection of chitinase activity and its characterization from Pseudomonas fluorescens of tea rhizosphere - Suganthi, M.; Arvinth, S.; Kumar, R. Raj (Journal of Plantation Crops, 2015)
<span style="color: black; line-height: 107%; font-family: ’Verdana’,’sans-serif’; font-size: 7.5pt; mso-bidi-language: AR-SA; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US;" lang="EN-GB">Please see the pdf file here: http://indsocplantationcrops.in/journal.php